Penerapan SMES untuk Load Frequency Control pada PLTMH Menggunakan Ant Colony Optimization - Faisal, Faisal; Ruswandi Djalal, Muhammad; Ali, Machrus (Jurnal FORTECH, 2024)
This research proposes an additional controller for load frequency control at a micro hydro power plant using PID-SMES. The PID-SMES parameters are optimized using smart methods called Ant Colony Optimization (ACO), which could find the optimal value of PID-SMES. In this paper four control approaches are compared which are P, PI, PID, SMES, and PID-SMES. From the simulation results, it can be obtained that overshoot of P controller is -0.0002193, with PI Controller is -0.0002183, with PD Controller is -0.0002139, with PID controller is -0.0002129, with SMES controller is -0.0001958, and with PID-SMES is -4.187e-05. ACO optimization results obtained fitness function value of 7.15e-09, with 50 iterations. The minimum value of the system performance function at each iteration is plotted on the convergence graph. In the simulation result, it can be concluded that the ACO algorithm could be quickly convergence on the 14th iteration or find the most optimal value at the 9th iteration. The PID-SMES controller proposed in this study has a significant influence in the damping of the oscillation of frequency deviation. Therefore, PID-SMES is appropriate to be applied to micro-hydro power plant.